A computational approach to determine key anatomic landmarks on pelvis and its application to acetabular orientation assessment and hip computational biomechanics. (July 2022) - Hua, Xijin; Li, Junyan
Highlights: Pelvic anatomic landmarks are important in hip orthopaedics, biomechanics and morphometric. A robust method for determining the pelvic anatomic landmarks was developed. The method can efficiently and accurately assess the native acetabular orientations. The fluid pressure in the cartilage supported most of loading during gait. The cartilage stresses and strain were predicted as 1.8 MPa and 0.12 during gait. Abstract: The determination of anatomic landmarks on the pelvis is an important procedure in orthopaedics, computational biomechanics and morphometrics. This study aimed to develop a robust method for determining the anatomic landmarks on the pelvis and demonstrate the application of the method in assessing the native acetabular orientation and developing multiscale computational modelling for hip biomechanics. Two Matlab algorithms, named "Pelvisor" and "Acetabulor", were developed to determine four anatomic landmarks on the pelvis and assess the acetabular orientation in the natural hip. The algorithms were then applied to: (1) assess the native acetabular orientations for a cohort of subjects; (2) develop a multiscale computational modelling to investigate the biomechanical behaviour of the biphasic cartilage in the natural hip joint. Results showed that the present method can accurately determine the key anatomic landmarks on the pelvis and assess the acetabular orientation in the natural hip joint. Significant differences in acetabular inclination and anteversion between males and females were identified, with larger orientations in females. The interstitial fluid pressure in the cartilage supported over 90% of loading during gait, and the stresses and strains within the solid matrix of the cartilage were as low as 1.8 MPa and 0.12, respectively.